Internationalization strategy of skypro to the west coast of the United States of America - Carujo, Joana (2018)
The underlying work project was carried out with the purpose of conducting an internationalization strategy of Skypro’s footwear to the West Coast of the United States. In order to do so, an in-depth situation analysis regarding the company was performed with the objective to have the most insightful view, followed by a preliminary screening and a country ranking analysis to select the optimal market. It was concluded that the US was the most attractive country by evaluating both, its macro and industry indicators. For the implementation strategy, various entry modes were analyzed. Lastly, specific activities were developed in order to complete the internationalization process.